Nutritional and health status among young Indian adults in Malaysia - Norimah A.Karim,; Khalidass M., (penerbit ukm, 2004)
A study was carried out to determine the relationship between nutritional status and health status among 80 young Indian adults (16 men and 64 women). Anthropometric measurements such as weight, height, waist and hip circumference were taken. Food intake, blood glucose and blood pressure were also evaluated. Birth weight was obtained from birth certificates or proxy. Results showed that mean weight, height, body mass index (BMI) and waist to hip ratio (WHR) for men were 64.9 + 9.1 kg, 1.7 + 0.1 m, 21.6 + 2.6 kg/m2 and 0.9 + 0.1, respectively. The anthropometric results reported for women were significantly (p < 0.05) lower than men except for BMI (50.7 + 9.9 kg, 1.6 + 0.1 m, 20.4 + 3.5 kg/m2, 0.8 + 0.1). Mean energy intake for men was 2215 + 323 kcal per day and was significantly (p < 0.05) higher than women (1594 + 292 kcal per day). Men and women fulfilled only 88% and 80% respectively of the energy recommendation for Malaysia. The nutrient of concern among women was iron, meeting only 46% of RDA. Mean blood glucose was 4.7 + 0.9 mmol/l in men while 4.4 + 0.6 mmol/l in women. Systolic (SBP) and diastolic blood pressure (DBP) was 112 + 8 mm Hg and 76 + 7 mm Hg in men and significantly higher than in women (103 + 10 mm Hg SBP, 70 + 8 mm Hg DBP). Positive associations were observed between birth weight and blood glucose, SBP DBP and BMI, however, the associations were not significant.